Aspectos sociales en el desarrollo sustentable de los sistemas de trabajo: colaboración universidad-sindicatos respecto del trabajo de las mujeres - Ana María Seifert (Universidade do Porto, 2009)
The sustainable development of work systems is not attainable without the well-being of workers´. This article addresses the importance of taking into account women´s work. Partial results from four studies carried out within a collaborative project with the three major Quebec labour federations serve to illustrate several social factors that affect women, either exclusively or in the majority. Participative methodology is used, including interviews and workplace observations. The results show how the analysis of work performed by women and the methods they use to facilitate work-family balance contributes to callinto question work organization systems that weaken work collectives and affect strategies to control/manage work and preserve mental health. We also discuss the importance of working with unions their contribution to the identification of emerging issues, the dissemination of research results and the generation of social pressure to improve working conditions.